Correlations between History of Contact with Infected Person and Measles Vaccination Status on the Risk of Measles Incidence in Children: Meta-Analysis - Ervia Fahma Dhony; Bhisma Murti; Hanung Prasetya (Masters Program in Public Health, 2024)
Background: Measles is a disease that can be prevented by immunization (VPD), which is highly contagious and often causes widespread outbreaks and can cause lifelong complications and death. Some evidence suggests that the risk of measles is due to contact history and vaccine status. This study aims to estimate the magnitude of the relationship between contact history and vaccine status with the incidence of measles in children, through a meta-analysis of primary studies conducted by previous authors.Subjects and Method: This research is a systematic review and meta-analysis with PICO as follows, Population: children. Intervention: contact history, vaccine status. Comparison: no contact history, no vaccine. Outcome: measles. The articles used in this research were obtained from three databases, namely PubMed, Google Scholar, and Science Direct, using the keys